A rare and often unrecognized cause of hematochezia and tenesmus in childhood: Solitary rectal ulcer syndrome - ERTEM ŞAHİNOĞLU, DENİZ (AMER ACAD PEDIATRICS, 2002)
Solitary rectal ulcer syndrome (SRUS) is an unusual disorder of childhood, which usually presents with rectal bleeding, mucous discharge, prolonged straining, tenesmus, and localized pain in the perineal area. After the first description by Cruveilhier, Madigan and Morson further detailed the clinical and pathologic features of SRUS in 1969. The pathogenesis of the syndrome is not well-understood. The postulated mechanism responsible for rectal prolapse in most cases seems to be excessive straining efforts during which high intra-abdominal pressure forces the anterior rectal mucosa firmly into the contracting puborectalis muscle. The anterior rectal mucosa is frequently forced into the anal canal and as a consequence becomes strangulated, causing congestion, edema, and ulceration. Histologically, the presence of fibromuscular obliteration of the lamina propria with disorientation of muscle fibers is characteristic, which could be secondary to chronic mechanical and ischemic trauma and inflammation by hard stools, and intussusception of the rectal mucosa. Although the syndrome is well-recognized in adults, the pediatric experience with this condition is limited and often remains unrecognized or misdiagnosed. A misdiagnosis has been reported in one fourth of adult cases, and the correct diagnosis usually delayed approximately 5 to 7 years. There are few pediatric case reports in English literature. Here, we describe 2 children with SRUS, aged 11 and 14 years, whose SRUS was diagnosed 2 and 6 years, respectively, after the onset of the first signs and symptoms.
Keywords: rectal bleeding; solitary rectal ulcer syndrome; CHILDREN; PROLAPSE